(untitled) - Medleau, Linda (London, 2006)
This clinical reference summarizes the symptoms, diagnosis, and treatment of 188 skin problems and diseases commonly seen in cats and dogs. Hundreds of color photographs illustrate the clinical presentation. Originally published as Color atlas of small animal dermatology in 2001; the second edition adds a final chapter of post-treatment images and suggested readings at the end of each chapter. Annotation ©2006 Book News, Inc., Portland
Keywords: Dogs,Chó,Cats; Diseases,Bệnh,Diseases